(2p + 7)(3p-9)
2p x 3p= 6p^2
2p x -9= -18p
7 x 3p=21p
7 x -9=-63
6p^2 - 18p + 21p - 63
6p^2 + 3p -63 is the answer.
Answer:
x >>>>>>>> f(x)
–9 >>>>>> 10
–7 >>>>>>> 0
0 >>>>>>>> –35
5 >>>>>>>> –60
Step-by-step explanation:
f(x) = –5(x + 7)
1. x = –9, f(x) =?
f(x) = –5(x + 7)
f(x) = –5(–9 + 7)
f(x) = –5(–2)
f(x) = 10
2. f(x) = 0, x =?
f(x) = –5(x + 7)
0 = –5(x + 7)
Divide both side by –5
0 / –5 = x + 7
0 = x + 7
Collect like terms
x = 0 – 7
x = –7
3. x = 0, f(x) =?
f(x) = –5(0 + 7)
f(x) = –5(7)
f(x) = –35
4. f(x) = –60, x =?
f(x) = –5(x + 7)
–60 = –5(x + 7)
Divide both side by –5
–60 / –5 = x + 7
12 = x + 7
Collect like terms
x = 12 – 7
x = 5
SUMMARY:
x >>>>>>>> f(x)
–9 >>>>>> 10
–7 >>>>>>> 0
0 >>>>>>>> –35
5 >>>>>>>> –60
Answer:
5 squares the times it by pi (pi equals 3.14 btw)
Step-by-step explanation:
5 squared is 25
Answer:
7.4 feets
Step-by-step explanation:
Distance from bottom of ladder to side of the house = d
θ = 62 ; height, h = 14
Using trigonometry :
Tan θ = opposite / Adjacent
Opposite = height ; adjacent = d
Tan 62° = 14 / d
1.8807264 * h = 14
d = 14 / 1.8807264
d = 7.44